Lumbar risk in handling iron bars in a steel company - Aguilar Maldonado, Miguel Ángel (2018)
Mr. Editor. Lumbar pain due to cargo handling constitutes an occupational health problem that results in reduced mobility and disability1,2,3. Thus, we inform you about a descriptive and cross-sectional study that aimed to determine the level of lumbar risk in the counting of iron bars, which we carried out in 2015 in the warehouse of the city of Pisco of the steel company Aceros Arequipa. Forty workers participated in the daily activity of counting iron bars in a standing and bending position, lifting bars of 30 kg. The INSHT method (National Institute for Safety and Hygiene in the Workplace of Spain) 1 was used in the determination of the level of lumbar risk with the data: weight of the load, posture, vertical displacement, trunk rotation, grip of the load, frequency, distance transported, according to the NIOSH equation that allows calculating an elevation index that provides the level of risk associated with a manual lifting task (quotient between weight of lifted load and recommended weight limit).